ANALISIS GAYA KEPEMIMPINAN KLASIK DAN SITUASIONAL - Handayani, Hany Tutut; Suherman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Leadership is a key element in organizational success. Various approaches have been developed to understand the role of leaders in influencing individual and group behavior. Among the most common approaches are classical and situational leadership styles, which reflect two different perspectives on how leaders can achieve optimal effectiveness in various situations. The purpose of this analysis is to analyze the differences between classical and situational leadership styles in various organizational contexts. This study uses a qualitative approach by conducting a review of various literature and references related to classical and situational leadership styles. The results of the analysis show that classical and situational leadership styles offer different approaches to leading an organization. Classical leadership tends to prioritize tight control, hierarchical structure, and clear commands, while situational leadership offers greater flexibility by adjusting the leadership style based on the conditions and needs of subordinates.